Composite material, rotary electrical machine, motor, electrical power generator and passive element

The composite material enhances bending strength by using coated metal particles with a high dicyclopentenyl group content polyester resin and a low dicyclopentenyl group content polyester resin, addressing the trade-off between resin strength and adhesive strength in existing composite materials.

JP2025044405AActive Publication Date: 2025-04-02KK TOSHIBA
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
JP2023151958
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-09-20
Publication Date
2025-04-02
Estimated Expiration
2043-09-20

AI Technical Summary

Technical Problem

Existing composite materials made of resin and metal particles face challenges in achieving high strength due to the trade-off between the strength of the polyester resin and the adhesive strength between the resin and metal particles.

Method used

A composite material is developed, comprising coated metal particles and polyester resin, where the coated metal particles include metal particles coated with polyester resin B, which has a high dicyclopentenyl group content for strong bonding, and polyester resin A, which has a lower dicyclopentenyl group content and a higher fumaric acid component ratio for improved bending strength.

Benefits of technology

The composite material achieves significantly improved bending strength compared to conventional composite materials, allowing for the creation of high-strength materials suitable for applications requiring strength and magnetic properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025044405000001_ABST
    Figure 2025044405000001_ABST
Patent Text Reader

Abstract

To provide a highly strong material in which resin and metal particles are composited.SOLUTION: There is provided according to one embodiment a composite material. The composite material includes metal particles and polyester resin so that, when the composite material is smashed, it is divided into a first polyester resin group containing polyester resin adhering to the metal particles and extracted and a second polyester resin group having a less metal content than the first polyester resin group.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] FIELD Embodiments of the present invention relate to a composite material, a rotating electrical machine, a motor, a generator, and a passive element. [Background technology]

[0002] There is a demand for high-strength materials that combine resin and metal particles. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2017-59816 A Summary of the Invention [Problem to be solved by the invention]

[0004] The problem to be solved by the present invention is to provide a high-strength material that is a composite of resin and metal particles. [Means for solving the problem]

[0005] According to one embodiment, a composite material is provided, which includes metal particles and polyester resin, and is divided into a first polyester resin group containing polyester resin that adheres to the metal particles and is extracted when the composite material is crushed, and a second polyester resin group having a lower metal content than the first polyester resin group. [Brief explanation of the drawings]

[0006] [Figure 1] FIG. 2 is a schematic diagram of a composite material according to the first embodiment. [Figure 2] FIG. 1 is a schematic diagram of a composite material being crushed. [Figure 3] FIG. 2 is a diagram showing the strength of the composite material according to the first embodiment and the strength of the composite material according to the conventional example. [Figure 4]FIG. 2 is a schematic diagram showing an example in which polyester resin B covers at least a portion of metal particles. [Figure 5] FIG. 1 is an example of a basic conceptual diagram of a composite material when flat magnetic metal particles are used. [Figure 6] FIG. 1 is a conceptual diagram showing the orientation of flat magnetic metal particles. [Figure 7] FIG. 1 is a block diagram illustrating an example of a motor system. [Figure 8] FIG. 1 is a conceptual diagram of a motor. [Figure 9] FIG. 2 is a conceptual diagram of a motor core. [Figure 10] This is an example of a conceptual diagram of a transformer. [Figure 11] 1 is an example of a conceptual diagram of an inductor. [Figure 12] 1 is an example of a conceptual diagram of a generator. [Figure 13] 10 is a diagram showing a preferred example of the relationship between the direction of magnetic flux and the arrangement direction of a composite material 100. FIG. DETAILED DESCRIPTION OF THE INVENTION

[0007] Hereinafter, embodiments will be described with reference to the drawings. Note that the present invention is not limited to the embodiments. Identical parts in the drawings are assigned the same numbers, and detailed descriptions thereof will be omitted as appropriate, and different parts will be described. Note that the drawings are schematic or conceptual, and the relationship between the thickness and width of each part, the size ratio between parts, etc. are not necessarily the same as those in reality. Furthermore, even when the same part is shown, the dimensions and ratios of each part may be different depending on the drawing.

[0008] Furthermore, in this specification, in describing substances contained in polyester resins, substances that are contained in the polyester skeleton are referred to as "components," and may be described as, for example, "dicarboxylic acid components."

[0009] In this specification, the "proportion" of the polyester resin is basically based on the volume ratio. When the volume ratio is used as the basis, the description is given in vol%. However, the proportion of the polyester resin phase 20 in the composite material 100 is described based on the mass ratio and is given in wt%.

[0010] (First embodiment) According to this embodiment, a composite material is provided. In this embodiment, the composite material includes coated metal particles and polyester resin A. The coated metal particles include metal particles and polyester resin B that coats at least a portion of the metal particles. Polyester resin A is present between multiple coated metal particles.

[0011] Fig. 1 is a schematic diagram of a composite material 100 according to this embodiment. Polyester resin B22 coats at least a portion of metal particles 11. Fig. 1 illustrates an example in which polyester resin B22 coats the entire metal particles 11. Polyester resin A21 bonds between coated metal particles 30, which are a combination of metal particles 11 and polyester resin B22 that coats at least a portion of metal particles 11.

[0012] The content of dicyclopentenyl groups in polyester resin B22 is preferably higher than the content of dicyclopentenyl groups in polyester resin A21. The contents of dicyclopentenyl groups in polyester resin A21 and polyester resin B22 can be analyzed using a pyrolysis gas chromatography mass spectrometer (Py-GC-MS). In a pyrogram obtained as a result of analysis using the pyrolysis gas chromatography mass spectrometer, the peak intensity representing dicyclopentenyl groups in polyester resin B22 is more preferably at least 1 time the peak intensity representing dicyclopentenyl groups in polyester resin A21.

[0013] It is preferable that polyester resin A21 contains almost no dicyclopentenyl groups or significantly less than polyester resin B22. Specifically, the peak intensity of polyester resin A21 obtained in a pyrogram by Py-GC-MS is preferably 1 / 10, and even more preferably 1 / 30, of that of polyester resin A21. In polyester resins A21 and B22, a high dicyclopentenyl group content reduces the viscosity of the unsaturated polyester, which is thought to facilitate its penetration into metal particles. It is also believed that dicyclopentenyl groups contribute to adhesion to metal particles. Furthermore, by imparting flexibility, it is expected to reduce the thermal expansion difference between metal particles and reduce defects during manufacturing. Therefore, although polyester resin B22 with a high dicyclopentenyl group content has a lower bending strength, it is expected to have a stronger bond strength with metal particles 11. Therefore, by making the peak intensity ratio of the dicyclopentenyl group contained in polyester resin A21 and the dicyclopentenyl group contained in polyester resin B22 have the above-mentioned relationship, the composite material 100 of this embodiment is expected to have improved bending strength compared to conventional composite materials.

[0014] Polyester resin A21 and polyester resin B22 contain a dicarboxylic acid component. The dicarboxylic acid component includes a succinic acid component and a fumaric acid component. The amount of fumaric acid relative to the succinic acid component in polyester resin A21 is preferably greater than the amount of fumaric acid relative to the succinic acid component in polyester resin B22. The dicarboxylic acid components contained in polyester resin A21 and polyester resin B22 can be analyzed using a pyrolysis gas chromatography mass spectrometer (Py-GC-MS). In this specification, the amount of fumaric acid relative to the succinic acid component is referred to as the F value, and is defined as F value = (detected amount of fumaric acid component / detected amount of succinic acid component). The F value is the peak intensity ratio of the fumaric acid component to the succinic acid component in a pyrogram obtained by analysis using the pyrolysis gas chromatography mass spectrometer. The F value in polyester resin A21 is more preferably 1 or more and 5 or less. The F value in polyester resin B is more preferably 1 or more and 3 or less. Furthermore, the F value of polyester resin A21 is preferably 1 to 7 times, and more preferably 1 to 10 times, the F value of polyester resin B22. In polyester resins A21 and B22, the larger the F value, i.e., the greater the amount of fumaric acid, the more crosslinked sites there are. Therefore, polyester resin A21 with a larger F value has a higher bending strength. Therefore, by adjusting the F values ​​of polyester resin A21 and polyester resin B22 as described above, the composite material 100 of this embodiment is expected to have improved bending strength compared to conventional composite materials.

[0015] The dicyclopentenyl group content and the F value are independent quantities. The resin according to this embodiment has a main chain of fumaric acid and succinic acid. The amount of dicyclopentenyl groups added can be varied regardless of the amount of fumaric acid and succinic acid, and the structures of fumaric acid, succinic acid, and dicyclopentenyl groups are maintained before and after crosslinking of the resin. The main chain of polyester resin A21 is primarily composed of succinic acid (butanedioic acid), fumaric acid (2-butenedioic acid), and propanediol. Crosslinking agents used for polyester resin A21 include styrene, diallyl phthalate (DAP), and triallyl cyanurate (TAC). Polyester resin A21 may contain compounds other than polyesters. However, it is preferable that the proportion of polyester resin is 50 vol% or more. Polyester resin A21 is a non-dicyclopentadiene (DCPD)-based unsaturated polyester, such as Sundoma 518-20. Polyester resin B22 is primarily composed of succinic acid (butanedioic acid), fumaric acid (2-butenedioic acid), propanediol, and hydroxydicyclopentadiene. Crosslinking agents used for crosslinking include styrene, diallyl phthalate (DAP), and triallyl cyanurate (TAC). Polyester resin B22 may contain compounds other than polyester. However, it is preferable that the proportion of polyester resin is 10% or more by volume. Polyester resin B22 is a dicyclopentadiene (DCPD)-based unsaturated polyester, examples of which include Polyhope SD4200 (manufactured by Japan Composite), Sundoma 5595(A)PT, and Sundoma CN-703 (all manufactured by DIC Materials), and U-Pica 7123 (manufactured by Japan U-Pica). Furthermore, when Polyhope SD4200 is used as resin B, Sundoma 5595(A)PT, Sundoma CN-703, or U-Pica 7123 can be used as resin A. However, these are examples that satisfy the characteristic conditions of polyester resins A21 and B, and the actual materials used for polyester resins A21 and B are not limited to these.

[0016] By making the peak intensity ratio or F value between the dicyclopentenyl groups contained in polyester resin A21 and the dicyclopentenyl groups contained in polyester resin B22 have the above-mentioned relationship, coated metal particles 30, in which metal particles 11 are coated with polyester resin B22, which has a high bonding strength with metal particles 11, are bonded with polyester resin A21, which has fewer dicyclopentenyl groups and / or a large F value, and therefore the composite material 100 of this embodiment is expected to have improved bending strength compared to conventional composite materials.

[0017] The composite material 100 is produced by bonding coated metal particles 30 obtained by coating metal particles 11 with polyester resin B22, which has high adhesive strength with the metal particles 11, with polyester resin A21, which has fewer dicyclopentenyl groups and / or a larger F value than polyester resin B22.

[0018] Once the composite material 100 is produced, it can be pulverized to examine the compositions of the polyester resin A21 and the polyester resin B22. Figure 2 is a schematic diagram of the composite material 100 after pulverization.

[0019] When the composite material 100 is pulverized, it can be roughly divided into a group (first polyester resin group 41) containing polyester resins extracted by adhering to the metal particles 11 and a group (second polyester resin group 42) containing less metal particles 11 than the first polyester resin group 41. The second polyester resin group 42 may not contain metal particles 11. In this case, the group containing polyester resins extracted by adhering to the metal particles 11 may be referred to as the first polyester resin group 41, and the group containing polyester resins extracted without adhering to the metal particles 11 may be referred to as the second polyester resin group 42. Although the metal particles 11 may be pulverized or deformed when the composite material 100 is pulverized, the metal particles after pulverization and deformation may be described herein as being the same as the metal particles 11 before pulverization. The composite material 100 is pulverized using a pestle or the like, and can be pulverized to a size of, for example, 1 mm square or less.

[0020] If the metal particles 11 are magnetic, it is possible to separate the pulverized composite material 100 into a first polyester resin group 41 that is attracted to the magnet and a second polyester resin group 42 that is not attracted to the magnet by bringing a magnet close to the pulverized composite material 100. Alternatively, wet separation can be performed by placing the pulverized composite material 100 in a liquid and adjusting the specific gravity of the liquid appropriately. For example, the pulverized composite material 100 can be placed in water to separate the first polyester resin group that floats on the water and the second polyester resin group that sinks. Alternatively, the pulverized composite material 100 can be dispersed in a liquid such as water and separated by centrifugation.

[0021] As described above, there are several methods for separating the first polyester resin group 41 and the second polyester resin group 42, and the separation method is not particularly limited as long as it can separate the resins into the first polyester resin group 41 and the second polyester resin group 42. In this case, the first polyester resin group 41 may contain, in addition to resin B22 attached to metal particles 11, resin A21 with resin B22 attached thereto, resin A21 alone, resin B22 alone, etc., but the proportion of polyester resin B22 contained in the first polyester resin group 41 is higher than that of the second polyester resin group 42.

[0022] Therefore, when the composite material 100 according to this embodiment is pulverized, the first polyester resin group 41 may have a higher content of dicyclopentenyl groups because it contains a larger amount of polyester resin B22 than the second polyester resin group 42. The contents of dicyclopentenyl groups in the first polyester resin group 41 and the second polyester resin group 42 can be analyzed using pyrolysis gas chromatography.

[0023] Furthermore, when the composite material 100 according to this embodiment is pulverized, since the second polyester resin group 42 has a higher proportion of polyester resin A21 than the first polyester resin group 41, the amount of fumaric acid components relative to succinic acid components (F value) in the second polyester resin group 42 may be greater than the amount of fumaric acid components relative to succinic acid components (F value) in the first polyester resin group 41.

[0024] The contents of succinic acid and fumaric acid components in the first polyester resin group and the second polyester resin group 42 can be analyzed using pyrolysis gas chromatography. In this case, the F value of the first polyester resin group 41 is more preferably 1 or more and 3 or less. On the other hand, since the second polyester resin group 42 contains a large amount of polyester resin A21, the F value is more preferably 1 or more and 5 or less.

[0025] Furthermore, when comparing the F value in the first polyester resin group 41 with the F value in the second polyester resin, the F value in the second polyester resin group 42 is preferably 1 to 7 times, and more preferably 1 to 10 times, the F value in the first polyester resin.

[0026] However, these values ​​are values ​​expected in an ideal case where the first polyester resin group 41 does not contain polyester resin A21 and the second polyester resin group 42 does not contain polyester resin B22. However, when the composite material 100 is actually pulverized, it is considered that resin A may be contained in the first polyester resin group 41 and resin B may be contained in the second polyester resin group 42, as shown in FIG. 2 . Therefore, the F value of the resin group actually extracted as the first polyester resin group may be higher than the F value of the ideal first polyester resin group 41. Similarly, the F value of the resin group actually extracted as the second polyester resin group 42 may be lower than the F value of the ideal second polyester resin group 42. Therefore, it should be noted that the value obtained by dividing the F value of the resin group actually extracted as the second polyester resin group 42 by the F value of the resin group actually extracted as the first polyester resin may be smaller than the value obtained by dividing the F value of the ideal second polyester resin group 42 by the F value of the ideal first polyester resin group 41.

[0027] FIG. 3 shows the strength of the composite material 100 according to the present embodiment and the composite material 100 according to a conventional example. The conventional example shows a composite material 100 prepared without coating the metal particles 11 with a resin (corresponding to polyester resin B in this embodiment) different from the bonding polyester resin (corresponding to polyester resin A in this embodiment). Here, the composite material 100 according to the conventional example was prepared by the method described below in Comparative Example 1. Two test pieces measuring approximately 15 mm × 120 mm × 2 mm were prepared for each of the composite materials, and their strength was evaluated by a three-point bending test. The test pieces of the composite material 100 according to the present embodiment were designated as test pieces A and B, and the test pieces of the composite material 100 according to the conventional example were designated as test pieces C and D. Comparing the average values ​​of test pieces A and B with those of test pieces C and D, it was found that test pieces A and B according to the present embodiment had strengths more than twice those of test pieces C and D according to the conventional example.

[0028] Conventionally, composite materials of polyester resin and metal particles 11 have had the problem of low strength when the metal particle content is high. Increasing the strength of the polyester resin itself weakens the adhesive strength between the polyester resin and metal particles 11, while decreasing the strength of the polyester resin itself reduces the strength of the composite material. As a result, the composite material 100 according to the conventional example could not be applied to components requiring high strength. However, according to the present embodiment, the strength of the composite material 100 using polyester resin can be increased. The composite material 100 has a structure in which coated metal particles 30, in which metal particles 11 are at least partially coated with resin B satisfying the above-mentioned certain conditions, are bonded together by resin A satisfying the above-mentioned certain conditions, thereby realizing a high-strength material that combines resin and metal particles 11.

[0029] Composite material 100 has a structure in which coated metal particles 30, at least a portion of which is coated with resin B containing a relatively large amount of dicyclopentenyl groups, are bonded together with polyester resin A21 containing almost no dicyclopentenyl groups, making it possible to realize a high-strength material that combines resin and metal particles 11.

[0030] Alternatively, composite material 100 having a structure in which coated metal particles 30, in which metal particles 11 are at least partially coated with resin B having a relatively small F value, are bonded together with polyester resin A21 having a relatively large F value, can realize a high-strength material that combines resin and metal particles 11. The dicyclopentenyl group content and F value can be controlled independently, and it can be said that the dicyclopentenyl group content and F value are independent parameters.

[0031] However, an even stronger composite material 100 may be formed by bonding coated metal particles 30, in which metal particles 11 are at least partially coated with resin B containing a relatively small amount of fumaric acid components and a relatively large amount of dicyclopentenyl groups, with polyester resin A21 containing a relatively large amount of fumaric acid components and almost no dicyclopentenyl groups. In this case, the content of dicyclopentenyl groups in the first polyester resin group 41 is higher than the content of dicyclopentenyl groups in the second polyester resin group 42, and the F value in the second polyester resin group 42 is larger than the F value in the first polyester resin group 41.

[0032] Furthermore, the coated metal particles 30 may be such that the metal particles 11 are completely coated with polyester resin B22 as shown in FIG. 1, or such that the polyester resin B22 coats at least a portion of the metal particles 11, or such that the polyester resin B22 adheres to the metal particles 11 as shown in FIG. 4.

[0033] The metal particles 11 contain at least one metal selected from, for example, La, Ce, Pr, Nd, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, Lu, Hf, Ta, W, Re, Os, Ir, Pt, Au, Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Y, Zr, Nb, Mo, Tc, Ru, Rh, Pd, Ag, and Cd. The size of the metal particles 11 is not particularly limited, but is generally 1 μm or more and 100 μm or less in diameter. Depending on the application, the diameter may be smaller than 1 μm or larger than 100 μm. The shape of the metal particles 11 is also not limited. The metal particles 11 may be nearly spherical, flat, or fibrous.

[0034] For example, the metal particles 11 may be flat metal particles 10 containing at least one magnetic metal selected from Fe, Co, and Ni, having a thickness of 10 nm to 100 μm, an aspect ratio of 5 to 10,000, and a lattice distortion of 0.01% to 10%. In the composite material 100, the flat magnetic metal particles 10 are oriented in a manner in which the flat surfaces 10a are stacked side by side as much as possible, and the flat surfaces 10a of the flat magnetic metal particles 10 have magnetic anisotropy in one direction. Here, the flat magnetic metal particles 10 are flaky particles having a flaky shape.

[0035] The magnitude of the uniaxial magnetic anisotropy within the flat surfaces 10a is preferably 0.1 Oe or more and 10 kOe or less, more preferably 1 Oe or more and 1 kOe or less, and even more preferably 1 Oe or more and 100 Oe or less. Whether or not a material has magnetic anisotropy and the degree of magnetic anisotropy can be easily evaluated by measuring in different directions using, for example, a VSM. In a compact using ordinary flat particles, the flat surfaces 10a are magnetically isotropic, which is fundamentally different from the present embodiment. Having magnetic anisotropy within the flat surfaces 10a significantly improves the magnetic properties.

[0036] First, when the magnetic domain structure of the flat magnetic metal particle 10 is a multi-domain structure, magnetization progresses by magnetic domain wall displacement, but the coercive force is smaller in the easy axis direction within the flat surface 10a than in the hard axis direction, resulting in smaller losses (hysteresis losses). Furthermore, the magnetic permeability is greater in the easy axis direction than in the hard axis direction. Compared to isotropic flat magnetic metal particles, flat magnetic metal particles with magnetic anisotropy have a smaller coercive force, particularly in the easy axis direction, which reduces losses and is therefore preferable. Furthermore, the magnetic permeability is also higher, which is also preferable. In other words, by having magnetic anisotropy in the direction within the flat surface 10a, the magnetic properties are improved compared to isotropic materials. In particular, the magnetic properties are superior in the easy axis direction within the flat surface 10a than in the hard axis direction.

[0037] Next, when the magnetic domain structure of the flat magnetic metal particle 10 is a single magnetic domain structure, magnetization proceeds by rotational magnetization, and in this case, the coercive force in the hard axis direction within the flat surface 10a is smaller than that in the easy axis direction, resulting in small losses. When magnetization proceeds completely by rotational magnetization, the coercive force becomes zero, which results in zero hysteresis loss, which is preferable.

[0038] Whether magnetization progresses by domain wall motion (domain wall motion type) or rotational magnetization (rotational magnetization type) is determined by whether the magnetic domain structure is a multi-domain structure or a single-domain structure. Whether a multi-domain structure or a single-domain structure is determined by the size (thickness and aspect ratio) of the flat magnetic metal particles 10, their composition, the state of interaction between particles, and other factors. For example, the thinner the flat magnetic metal particles 10, the more likely they are to have a single-domain structure. A thickness of 10 nm to 1 μm, particularly 10 nm to 100 nm, is likely to result in a single-domain structure. In terms of composition, a composition with high crystalline magnetic anisotropy tends to maintain a single-domain structure even at a high thickness, while a composition with low crystalline magnetic anisotropy tends to have difficulty maintaining a single-domain structure unless the thickness is small. In other words, the thickness at which a single-domain structure or a multi-domain structure is formed varies depending on the composition. Furthermore, when the flat magnetic metal particles 10 are magnetically bonded to each other and the magnetic domain structure is stabilized, a single magnetic domain structure is more likely to be formed.

[0039] FIG. 5 shows an example of a basic conceptual diagram of a composite material using flat magnetic metal particles. FIG. 5(a) is a conceptual diagram of the composite material of this embodiment. FIG. 5(b) is a conceptual diagram of a flat magnetic metal particle 10 of this embodiment. FIG. 5(c) shows the behavior of the magnetization curve (BH curve) for both cases where magnetization progresses by domain wall motion and by rotational magnetization. Whether the magnetization behavior is domain wall motion or rotational magnetization can be easily determined as follows. First, magnetization measurements are performed by changing the direction of application of the magnetic field within the plane of the composite material 100 (a plane parallel to the flat surfaces of the flat magnetic metal particles), and the two directions (the two directions are at 90 degrees from each other) that produce the largest difference in the magnetization curves are found. Next, by comparing the curves for the two directions with those in FIG. 5(c), it is possible to determine whether the magnetization behavior is domain wall motion or rotational magnetization.

[0040] A conceptual diagram of the orientation of the flat magnetic metal particles 10 is shown in Figure 6. In this specification, it is defined that the closer the angle between the plane parallel to the flat surface 10a of the flat magnetic metal particle 10 and the plane of the composite material 100 is to 0 degrees, the more oriented the particle is. Specifically, the above-mentioned angle is determined for a large number of flat magnetic metal particles 10 (10 or more), and the average value is preferably between 0 degrees and 45 degrees, more preferably between 0 degrees and 30 degrees, and even more preferably between 0 degrees and 10 degrees.

[0041] Although the flat magnetic metal particles 10 have a flat shape, flat magnetic metal particles are preferable to spherical ones. In other words, the aspect ratio is preferably 5 or more and 10,000 or less, which increases the magnetic permeability. Furthermore, this is preferable because it increases the ferromagnetic resonance frequency and reduces ferromagnetic resonance loss. The thickness t is preferably 10 nm or more and 100 μm or less, more preferably 10 nm or more and 1 μm or less, and even more preferably 10 nm or more and 100 nm or less. This is preferable because it sufficiently reduces eddy current loss when a magnetic field is applied in a direction parallel to the flat surfaces 10 a. Furthermore, a smaller thickness t and a larger aspect ratio are preferable because the magnetic moment is confined in a direction parallel to the flat surfaces 10 a, facilitating the progression of rotational magnetization.

[0042] The aspect ratio refers to the ratio of the structure dimension (long dimension) in the direction in which the length of the flat magnetic metal particle 10 is longest to the structure dimension (short dimension) in the direction in which the length is shortest, i.e., "long dimension / short dimension." Therefore, the aspect ratio is always 1 or greater. In the case of a perfect sphere, both the long dimension and the short dimension are equal to the diameter of the sphere, so the aspect ratio is 1. The aspect ratio of a flat magnetic metal particle 10 is the diameter (long dimension) of the flat surface 10a divided by the thickness (short dimension). For the flat magnetic metal particle 10 shown in Figure 5, the aspect ratio is calculated as (((a+b) / 2) / t), where b is the minimum length within the flat surface 10a, a is the maximum length, and t is the thickness. Here, (a+b) / 2 is the average of the minimum length b and the maximum length a within the flat surface 10a. The aspect ratio and thickness t can be easily evaluated by observation using a transmission electron microscope (TEM) or a scanning electron microscope (SEM).

[0043] The lattice distortion of the flat magnetic metal particles 10 is preferably 0.01% to 10%, more preferably 0.01% to 5%, even more preferably 0.01% to 1%, and even more preferably 0.01% to 0.5%. This is preferable because it makes it easier to impart a moderately large magnetic anisotropy and improves the above-mentioned magnetic properties.

[0044] Lattice strain can be calculated by detailed analysis of the line width obtained by X-ray diffraction (XRD). That is, by performing a Halder-Wagner plot or a Hall-Williamson plot, the contribution of the line width broadening can be separated into the crystal grain size and the lattice strain. This allows the lattice strain to be calculated. The Halder-Wagner plot is preferable from the viewpoint of reliability. For details on the Halder-Wagner plot, see, for example, N.C. Halder, C.N.J. Wagner, Acta Cryst. 20 (1966) 312-313. Here, the Halder-Wagner plot is expressed by the following formula:

[0045]

number

[0046] That is, β2 / tan2θ is plotted on the vertical axis and β / tanθ sinθ on the horizontal axis, and the crystal grain size D is calculated from the slope of the approximate line, and the lattice strain ε is calculated from the vertical intercept. When the lattice strain (root mean square) according to the Halder-Wagner plot of the above formula is 0.01% to 10%, more preferably 0.01% to 5%, even more preferably 0.01% to 1%, and even more preferably 0.01% to 0.5%, it is easy to impart a moderately large magnetic anisotropy, and the above-mentioned magnetic properties are improved, which is preferable.

[0047] The lattice strain analysis described above is effective when multiple peaks can be detected by XRD. However, analysis is difficult when the peak intensity is weak and only a single peak can be detected (e.g., only one peak is detected). In such cases, it is preferable to calculate the lattice strain using the following procedure. First, the composition is determined using inductively coupled plasma (ICP) emission spectroscopy or energy dispersive X-ray spectrometry (EDX) to calculate the composition ratios of the three magnetic metal elements Fe, Co, and Ni. (If there are only two magnetic metal elements, two composition ratios are used. If there is only one magnetic metal element, one composition ratio (=100%) is used.) Next, the ideal lattice spacing d0 is calculated from the Fe-Co-Ni composition (see literature values, etc.; in some cases, an alloy with that composition is prepared and the lattice spacing is measured). The amount of strain can then be calculated by calculating the difference between the lattice spacing d of the measured sample peak and the ideal lattice spacing d0. In other words, in this case, the amount of strain is calculated as (d - d0) / d0 × 100(%). As mentioned above, the lattice strain analysis should be performed using either of the two methods mentioned above depending on the state of the peak intensity, and in some cases it is preferable to use both methods in combination.

[0048] The lattice spacing in the flat surface 10a of the flat magnetic metal particle varies depending on the direction, and the maximum lattice spacing d max and the minimum lattice spacing d min The percentage difference (=(d max -d min ) / d min × 100(%)) is preferably 0.01% or more and 10% or less, more preferably 0.01% or more and 5% or less, even more preferably 0.01% or more and 1% or less, and even more preferably 0.01% or more and 0.5% or less. This is preferable because it makes it easier to impart a moderately large magnetic anisotropy and improves the above-mentioned magnetic properties.

[0049] The lattice spacing can be easily determined by XRD measurement. By performing this XRD measurement on the composite material 100 while changing the direction in the plane, the difference in lattice constant depending on the direction can be determined.

[0050] The crystallites of the flat magnetic metal particles 10 are preferably either stringed together in one direction within the flat surface 10a, or are rod-shaped and oriented in one direction within the flat surface 10a. This is preferable because it makes it easier to impart a moderately large magnetic anisotropy and improves the above-mentioned magnetic properties.

[0051] The flat magnetic metal particles 10 contain two magnetic metals, Fe and Co, and preferably contain 10 atomic % to 60 atomic % of Co relative to the total amount of Fe and Co, and more preferably 10 atomic % to 40 atomic % of Co. This is preferable because it makes it easier to impart a moderately large magnetic anisotropy and improves the above-mentioned magnetic properties. In addition, Fe-Co systems are preferable because they make it easier to achieve high saturation magnetization. Furthermore, when the composition range of Fe and Co falls within the above range, it is preferable because higher saturation magnetization can be achieved.

[0052] It is preferable that the flat magnetic metal particles 10 contain at least one non-magnetic metal selected from the group consisting of Mg, Al, Si, Ca, Zr, Ti, Hf, Zn, Mn, Ba, Sr, Cr, Mo, Ag, Ga, Sc, V, Y, Nb, Pb, Cu, In, Sn, and rare earth elements.

[0053] This can improve the thermal stability and oxidation resistance of the flat magnetic metal particles 10. Among these, Al and Si are particularly preferred because they are easily dissolved in Fe, Co, and Ni, which are the main components of the flat magnetic metal particles 10, and contribute to improving the thermal stability and oxidation resistance.

[0054] In order to induce magnetic anisotropy, one method is to make the crystallinity of the flat magnetic metal particles 10 as amorphous as possible and then induce magnetic anisotropy in one in-plane direction using a magnetic field or distortion. For this purpose, it is desirable to make the flat magnetic metal particles 10 as easy to make amorphous as possible. From this perspective, it is preferable that the magnetic metal contained in the flat magnetic metal particles 10 contains at least one additive metal selected from B, Si, C, Ti, Zr, Hf, Nb, Ta, Mo, Cr, Cu, W, P, N, and Ga, each of which is 0.001 atomic % or more and 25 atomic % or less of the total amount of the magnetic metal, non-magnetic metal, and additive metal.

[0055] It is preferable that the flat surfaces 10a of the flat magnetic metal particles 10 are crystalline oriented. The orientation direction is preferably a (110) plane orientation or a (111) plane orientation, with a (110) plane orientation being more preferable. If the crystal structure of the flat magnetic metal particles 10 is a body-centered cubic structure (bcc), a (110) plane orientation is preferable, and if the crystal structure of the flat magnetic metal particles 10 is a face-centered cubic structure (fcc), a (111) plane orientation is preferable. This is preferable because it makes it easier to impart a moderately large magnetic anisotropy and improves the above-mentioned magnetic properties.

[0056] Furthermore, more preferred orientation directions are the (110)

[0111] direction and the (111)

[0110] direction, with the (110)

[0111] direction being more preferred. When the crystal structure of the flat magnetic metal particles 10 is a body-centered cubic structure (bcc), orientation in the (110)

[0111] direction is preferred, and when the crystal structure of the flat magnetic metal particles 10 is a face-centered cubic structure (fcc), orientation in the (111)

[0110] direction is preferred. This is preferred because it makes it easier to impart a moderately large magnetic anisotropy and improves the above-mentioned magnetic properties. In this specification, the "(110)

[0111] direction" means that the slip plane is the (110) plane or a plane crystallographically equivalent thereto, i.e., the {110} plane, and the slip direction is the

[0111] direction or a direction crystallographically equivalent thereto, i.e., <111> The same applies to the (111)

[0110] direction. That is, the slip plane is the (111) plane or a crystallographically equivalent plane, i.e., the {111} plane, and the slip direction is the

[0110] direction or a crystallographically equivalent direction, i.e., <110> It refers to the direction.

[0057] The crystal structure of the flat magnetic metal particles 10 is preferably a body-centered cubic structure, but more preferably a "crystal structure of a mixed phase of body-centered cubic and face-centered cubic structures" that partially has a face-centered cubic crystal structure. This is preferable because it makes it easier to impart a moderately large magnetic anisotropy and improves the above-mentioned magnetic properties.

[0058] As described above, the composite material 100 of this embodiment is a composite material containing metal particles and polyester resin, and when the composite material is pulverized, it is divided into a first polyester resin group containing polyester resin that adheres to the metal particles and is extracted, and a second polyester resin group having a lower content of metal particles 11 than the first polyester resin group 41. With such a composite material, when the metal particles are magnetic, it is possible to realize a high-strength composite material 100 that has excellent properties, particularly in terms of high magnetic permeability and low loss.

[0059] The phase present between the metal particles 11 and containing polyester resin A21 and polyester resin B22 is designated as polyester resin phase 20. Considering magnetic properties such as saturation magnetization and magnetic permeability, thermal stability, and mechanical properties, the polyester resin phase 20 preferably accounts for 0.01 wt% to 80 wt%, more preferably 0.1 wt% to 60 wt%, and even more preferably 0.1 wt% to 40 wt% of the composite 100. In particular, when flat magnetic metal particles 10 are used as the metal particles 11, if the proportion of the polyester resin phase 20 in the composite 100 is too high, the proportion of the flat magnetic metal particles 10 responsible for magnetism will decrease, which undesirably reduces the saturation magnetization and magnetic permeability of the composite 100. Conversely, if the proportion of the polyester resin phase 20 is too low, the bonding between the flat magnetic metal particles 10 and the polyester resin phase 20 will be weak, which is undesirable from the standpoint of thermal stability and mechanical properties such as strength and toughness.

[0060] When flat magnetic metal particles 10 are used as metal particles 11, polyester resin phase 20 contains at least one of oxygen (O), carbon (C), nitrogen (N), hydrogen (H), cobalt (Co), and fluorine (F). It is preferable that polyester resin phase 20 has a higher electrical resistivity than flat magnetic metal particles 10. This is because it can reduce eddy current loss in flat magnetic metal particles 10. Since polyester resin phase 20 surrounds flat magnetic metal particles 10, it is preferable because it can improve the oxidation resistance and thermal stability of flat magnetic metal particles 10. Among these, those containing oxygen are more preferable from the viewpoint of high oxidation resistance and high thermal stability. Since polyester resin phase 20 also plays a role in mechanically bonding flat magnetic metal particles 10 together, it is also preferable from the viewpoint of high strength.

[0061] (Second embodiment) According to this embodiment, a rotating electric machine is provided. The system and device of this embodiment include the composite material 100 of the first embodiment. Therefore, descriptions of parts overlapping with those of the first embodiment will be omitted, or parts common to the first embodiment will be described using the same reference numerals. Components of the composite material 100 included in this system and device include, for example, rotating electric machines (e.g., motors, generators, etc.), transformers, inductors, choke coils, and filter cores, as well as magnetic wedges for rotating electric machines. FIG. 7 shows a block diagram of a motor system 1000 as an example of a rotating electric machine system. A motor system is a system including a control system for controlling the rotation speed and power (output power) of a motor. Methods for controlling the rotation speed of a motor include control using a bridge servo circuit, proportional current control, voltage comparison control, frequency synchronization control, and PLL (Phase Locked Loop) control. As an example, a PLL control method is shown in FIG. 7. A motor system 1000 that controls the motor rotation speed using a PLL includes a motor, a rotary encoder that converts the mechanical displacement of the motor's rotation into an electrical signal to detect the motor rotation speed, a phase comparator that compares the motor rotation speed given by a command with the motor rotation speed detected by the rotary encoder and outputs the difference between the rotation speeds, and a controller that controls the motor to minimize the difference in rotation speed. Meanwhile, methods for controlling the motor's power include PWM (Pulse Width Modulation) control, PAM (Pulse Amplitude Modulation) control, vector control, pulse control, bipolar drive, pedestal control, and resistance control. Other control methods include microstep drive control, multiphase drive control, inverter control, and switching control. As an example, an inverter control method is shown in Figure 7.A motor system 1000 that controls the power of a motor using an inverter includes an AC power supply, a rectifier that converts the output of the AC power supply into DC current, an inverter circuit that converts the DC current into AC at an arbitrary frequency, and a motor controlled by the AC current.

[0062] 8 shows a conceptual diagram of a motor 200 as an example of a rotating electric machine. A first stator 210 and a first rotor 220 are arranged in the motor 200. While the figure shows an inner rotor type in which the rotor is arranged inside the stator, an outer rotor type in which the rotor is arranged outside the stator may also be used.

[0063] FIG. 9 shows a conceptual diagram of a motor core. The motor core includes the cores of a stator and a rotor. This point will be explained below with reference to FIG. 9. FIG. 9(a) is an example of a cross-sectional conceptual diagram of a first stator 210. The first stator 210 has a core and a winding. The winding is wound around a part of a protrusion on the inside of the core. The composite material 100 of the first embodiment can be disposed within this core. FIG. 9(b) is an example of a cross-sectional conceptual diagram of a first rotor 220. The first rotor 220 has a core and a winding. The winding is wound around a part of a protrusion on the outside of the core. The composite material 100 of the first embodiment can be disposed within this core.

[0064] 8 and 9 merely show examples of motors, and the application of the composite material 100 is not limited to these. The composite material 100 can be applied to all kinds of motors as a core that makes it easier to guide magnetic flux.

[0065] Furthermore, similar to motor cores, the composite material 100 of this embodiment can be applied to any type of passive element to facilitate the conduction of magnetic flux or to utilize high magnetic permeability. Passive elements are electronic elements that do not have active functions such as amplification or conversion of electrical energy, and are a general term for, for example, resistors, capacitors, coils, transformers, and inductors. A conceptual diagram of a transformer 300 is shown in FIG. 10, and a conceptual diagram of an inductor 400 is shown in FIG. 11. These are merely examples.

[0066] FIG. 12 shows a conceptual diagram of a generator 500 as an example of a rotating electrical machine. The generator 500 includes either or both of a second stator 530 using the composite material 100 of the first embodiment and a second rotor 540 using the composite material 100 of the first embodiment. In the figure, the second rotor 540 is disposed inside the second stator 530, but it may be disposed outside. The second rotor 540 is connected to a turbine 510 provided at one end of the generator 500 via a shaft 520. The turbine 510 is rotated, for example, by a fluid supplied from an external source (not shown). Note that instead of the turbine 510 being rotated by a fluid, the shaft 520 can also be rotated by transmitting dynamic rotation, such as regenerative energy from an automobile. Various known configurations can be employed for the second stator 530 and the second rotor 540.

[0067] The shaft 520 is in contact with a commutator (not shown) that is arranged on the opposite side of the second rotor 540 from the turbine 510. The electromotive force generated by the rotation of the second rotor 540 is boosted to a system voltage and transmitted as power for the generator 500 via a phase isolation bus (not shown) and a main transformer (not shown). Note that the second rotor 540 is charged with static electricity from the turbine 510 and axial current due to power generation. For this reason, the generator 500 is provided with brushes 550 for discharging the charge on the second rotor 540.

[0068] FIG. 13 also shows a preferred example of the relationship between the direction of magnetic flux and the arrangement direction of the composite material 100. First, in both the domain wall motion type and the rotational magnetization type, it is preferable to arrange the flat surfaces 10a of the flat magnetic metal particles 10 contained in the composite material in a direction that is as parallel as possible to the direction of magnetic flux. This is because eddy current loss can be reduced by minimizing the cross-sectional area of ​​the flat magnetic metal particles 10 that penetrate the magnetic flux. Furthermore, in the domain wall motion type, it is preferable to arrange the easy axis of magnetization (direction of the arrow) within the flat surfaces 10a of the flat magnetic metal particles 10 parallel to the direction of magnetic flux. This allows the material to be used in a direction that further reduces coercive force, thereby reducing hysteresis loss, which is preferable. It is also preferable to increase magnetic permeability. Conversely, in the rotational magnetization type, it is preferable to arrange the easy axis of magnetization (direction of the arrow) within the flat surfaces 10a of the flat magnetic metal particles 10 perpendicular to the direction of magnetic flux. This allows the material to be used in a direction that further reduces coercive force, thereby reducing hysteresis loss, which is preferable. In other words, it is preferable to understand the magnetization characteristics of the composite material 100, determine whether it is a domain wall motion type or a rotational magnetization type (the method of determination is as described above), and then arrange it as shown in FIG. 13. If the direction of the magnetic flux is complex, it may be difficult to arrange it exactly as shown in FIG. 13, but it is preferable to arrange it as shown in FIG. 13 as much as possible. It is preferable that the above arrangement method be applied to all systems and devices of this embodiment (for example, rotating electric machines such as various motors and generators (for example, motors, generators, etc.), transformers, inductors 400, transformers / transformers 300, cores of choke coils, filters, etc., magnetic wedges for rotating electric machines, etc.

[0069] To be applied to the system and device, the composite material 100 can be subjected to various processes. For example, in the case of a sintered body, it can be subjected to mechanical processes such as polishing and cutting, and in the case of a powder, it can be mixed with a resin such as epoxy resin or polybutadiene. Further, surface treatment can be performed as needed. Furthermore, winding can be performed as needed.

[0070] According to the system and device of this embodiment, it is possible to realize a motor system, motor, transformer, transformer / transformer 300, inductor 400, and generator having excellent characteristics (high efficiency, low loss).

[0071] (Example) Examples 1 and 2 of the present invention are described in more detail below, in comparison with a comparative example. Table 1 shows the metal particle size (metal particle diameter or flat magnetic metal particle thickness and aspect ratio), metal particle composition, product names used in polyester resins A and B, and strength measurement results from a three-point bending test for the composite materials obtained in the following examples and comparative examples. In the three-point bending test, two test pieces are prepared for each example and comparative example, and bending strength is measured. Measurements of the particle diameter of metal particles, etc., are calculated as the average value of a large number of particles based on TEM and SEM observations. The composition is comprehensively determined using EDX and ICP.

[0072] Example 1 The metal particles used were FeCrNi-based stainless steel (SUS304) powder. The particle size of the metal particles was approximately 20 μm. Furthermore, DIC Materials' Sundoma 518-20 was used as polyester resin A, and Japan Composite's Polyhope SD4200 was used as polyester resin B.

[0073] Predetermined amounts of raw materials, stainless steel powder and polyester resin B, are weighed out. 1 wt% of polyester resin B is weighed out relative to the stainless steel powder and dissolved in acetone to obtain a polyester solution. The stainless steel powder is then mixed with the polyester solution, placed in a container, and dried at 60°C. This is then heat-treated at 200°C for 2 hours to obtain coated stainless steel powder. This coated stainless steel powder is molded using polyester resin A and heat-treated to obtain a composite material. The composite material produced by the method of Example 1 is an example of a composite material related to the first embodiment.

[0074] Example 2 The metal particles used are FeCo-based flat magnetic metal particles. The resins used as polyester resin A and polyester resin B are the same as those in Example 1.

[0075] First, FeCo-based flat magnetic metal particles were prepared. A ribbon of Fe-Co-Si-B (Fe:Co = 70:30 wt%) was prepared using a single-roll quenching device. Next, this ribbon was cut to an appropriate size using a mixer. The cut ribbon pieces were then collected and crushed and rolled at 1000 rpm in an Ar atmosphere using a planetary mill equipped with ZrO2 balls and a ZrO2 container. The above cutting, crushing, and rolling processes were repeated to produce flat magnetic metal particles with a thickness of 10 nm and an aspect ratio of 1000. The resulting flat magnetic metal particles had a thickness of approximately 10 μm and an aspect ratio of approximately 1000. Polyester resin B was weighed out at 1 wt% relative to the flat magnetic particles and dissolved in acetone to obtain a polyester solution. The flat magnetic metal particles were then mixed with the polyester solution, placed in a container, and dried at 60°C. The mixture was then heat-treated at 200°C for 2 hours to obtain coated flat magnetic metal particles. These coated flat magnetic metal particles are molded using polyester resin A and subjected to the same heat treatment as in Example 1 to obtain a composite material. The composite material produced by the method of Example 2 is an example of a composite material when flat magnetic metal particles are used in the first embodiment.

[0076] (Comparative Example 1) The stainless steel powder used as the metal particles and the material used as the polyester resin A are the same as those in Example 1. In Comparative Example 1, the polyester resin B is not used.

[0077] The stainless steel powder is molded using polyester resin A, and a composite material is obtained by carrying out a heat treatment similar to that in Example 1. The composite material produced by the method of Comparative Example 1 is an example of a composite material referred to herein as a "composite material produced by a conventional method."

[0078] (Comparative Example 2) The flat magnetic metal particles used as the metal particles and the material used as the polyester resin A are the same as those in Example 2. In Comparative Example 2, no polyester resin B is used.

[0079] First, FeCo-based flat magnetic metal particles are prepared in the same manner as in Example 2. The obtained flat magnetic metal particles are molded using polyester resin A and subjected to the same heat treatment as in Example 1 to obtain a composite material.

[0080] [Table 1]

[0081] Table 1 shows the preparation conditions and the results of pulverization for Examples 1 and 2 and Comparative Examples 1 and 2.

[0082] When the composite material of Example 1 is crushed with a pestle or the like to a size of 1 mm square or less, it separates into metal particles with resin B attached, metal particles with resins A and B attached, resin A with resin B attached, resin A alone, resin B alone, and metal particles alone. If the metal particles are magnetic, bringing a magnet close to these aggregates will attract the metal particles and metal particles with resin B attached, metal particles with resins A and B attached, and metal particles with only resin A attached, and separate them into resin A with resin B attached, resin A alone, and resin B alone. At this time, resin A with resin B attached, resin A alone, and resin B alone may become entangled with metal particles, or metal particles may not be attracted to the magnet by chance, so complete separation may not be achieved. However, by separating the portions that are not attracted to the magnet from the portions that are attracted, the first polyester resin group and the second polyester resin group can be separated.

[0083] In this way, the fact that the composite material can be separated into the first polyester resin group and the second polyester resin group after being crushed is indicated by the symbol ○ in the column "Can it be separated by crushing?" in Table 1. In this example, because the metal particles contain Fe, separation was performed using a magnet.

[0084] The first polyester resin group and the second polyester resin group after separation were each measured by pyrolysis gas chromatography to obtain the contents of dicyclopentenyl groups, succinic acid components, and fumaric acid components contained in each. The value obtained by dividing the content of dicyclopentenyl groups contained in the second polyester resin group by the content of dicyclopentenyl groups contained in the first polyester resin group is shown in the "Dicyclopentenyl Group" column in Table 1. In Example 1, the content of dicyclopentenyl groups contained in the first polyester resin group was higher than the content of dicyclopentenyl groups contained in the second polyester resin group, and the value obtained by dividing the content of dicyclopentenyl groups contained in the second polyester resin group by the content of dicyclopentenyl groups contained in the first polyester resin group was approximately 1 / 20. The value obtained by dividing the F value of the second polyester resin group by the F value of the first polyester resin group is shown in the "F Value" column in Table 1. In Example 1, the F value in the second polyester resin group was larger than the F value in the first polyester resin group, and the value obtained by dividing the F value in the second polyester resin group by the F value in the first polyester resin group was 1.2.

[0085] In Example 2, as in Example 1, the first polyester resin group and the second polyester resin group could be separated using a magnet. Furthermore, the dicyclopentenyl group content of the first polyester resin group was higher than that of the second polyester resin group, and the value obtained by dividing the dicyclopentenyl group content of the second polyester resin group by the dicyclopentenyl group content of the first polyester resin group was approximately 1 / 15. The dicyclopentenyl group ratio value in the table for Example 2 in Example 2 is smaller than the dicyclopentenyl group ratio value in the table for Example 1. This is likely because Cr and Ni form a strong oxide film on the Fe surface, resulting in a higher amount of dicyclopentenyl polyester in the first polyester resin group, which has stronger adhesive strength between resin B and the metal particles. Furthermore, in Example 2, the F value of the second polyester resin group was higher than that of the first polyester resin group, and the value obtained by dividing the F value of the second polyester resin group by the F value of the first polyester resin group was 1.2.

[0086] In Comparative Examples 1 and 2, it was not possible to separate the first polyester resin group and the second polyester resin group. Thus, the inability to separate the first polyester resin group and the second polyester resin group after crushing the composite material is indicated by an x ​​in the "Can it be separated by crushing?" column in Table 1. Since the crushed composite material was not separable, it was not possible to measure the values ​​that should be listed in the "Dicyclopentenyl group" and "F value" columns in Table 1.

[0087] [Table 2]

[0088] Comparing the strength measurement results in Table 2 between Example 1 and Comparative Example 1, it is clear that the composite material of Example 1 has higher strength. Furthermore, comparing Example 2 and Comparative Example 2, it is clear that the composite material of Example 2 has higher strength. In Examples 1 and 2, the dicyclopentenyl content of the first polyester resin group that adheres to and is extracted from the metal particles is higher than that of the second polyester resin group, indicating that the first polyester resin group contains a large amount of polyester resin B, which has a strong bond strength with the metal particles. Furthermore, the F value of the second polyester resin group is larger than that of the first polyester resin group, indicating that the second polyester resin group contains a large amount of polyester resin A, which has a high flexural strength. Because the coated metal particles, in which metal particles are coated with polyester resin B, which has a strong bond strength with the metal particles, are bonded with polyester resin A, which has a high flexural strength, the flexural strength of the composite material of the example is greater than that of the composite material of the comparative example.

[0089] Although several embodiments of the present invention have been described, these embodiments are presented as examples and are not intended to limit the scope of the invention. These novel embodiments can be embodied in various other forms, and various omissions, substitutions, and modifications can be made without departing from the spirit of the invention. These embodiments and their modifications are included within the scope and spirit of the invention, and are also included in the scope of the invention and its equivalents as defined in the claims.

[0090] Furthermore, the present disclosure includes examples according to the following appendices.

[0091] [Appendix 1] A composite material comprising metal particles and a polyester resin, When the composite material is pulverized, it is divided into a first polyester resin group containing polyester resins that adhere to the metal particles and are extracted, and a second polyester resin group having a lower content of metal particles than the first polyester resin group.

[0092] [Appendix 2] the content of dicyclopentenyl groups in the first polyester resin group is higher than the content of dicyclopentenyl groups in the second polyester resin group; 1. A composite material as described in Appendix 1.

[0093] [Appendix 3] the amount of the fumaric acid component relative to the succinic acid component in the second polyester resin group is greater than the amount of the fumaric acid component relative to the succinic acid component in the first polyester resin group; 1. A composite material as described in Appendix 1 or Appendix 2.

[0094] [Appendix 4] the content of dicyclopentenyl groups in the first polyester resin group is higher than the content of dicyclopentenyl groups in the second polyester resin group; the amount of the fumaric acid component relative to the succinic acid component in the second polyester resin group is greater than the amount of the fumaric acid component relative to the succinic acid component in the first polyester resin group; 4. The composite material of any one of claims 1 to 3.

[0095] [Appendix 5] the amount of the fumaric acid component relative to the succinic acid component in the second polyester resin group is 1 to 10 times the amount of the fumaric acid component relative to the succinic acid component in the first polyester resin group; 5. The composite material of any one of claims 1 to 4.

[0096] [Appendix 6] the amount of the fumaric acid component relative to the succinic acid component in the second polyester resin group is 1 to 7 times the amount of the fumaric acid component relative to the succinic acid component in the first polyester resin group; 6. The composite material of any one of claims 1 to 5.

[0097] [Appendix 7] The metal particles contain at least one magnetic metal selected from Fe, Co, and Ni. 7. The composite material of any one of claims 1 to 6.

[0098] [Appendix 8] the metal particles are flat magnetic metal particles having a thickness of 10 nm or more and 100 μm or less, an aspect ratio of 5 or more and 10,000 or less, and a lattice distortion of 0.01% or more and 10% or less, The flat magnetic metal particles are oriented and have magnetic anisotropy in one direction within the oriented flat plane. 8. The composite material of any one of claims 1 to 7.

[0099] [Appendix 9] coated metal particles comprising metal particles and polyester resin B that coats at least a portion of the metal particles; a polyester resin A present between a plurality of the coated metal particles; A composite material comprising: When the composite material is pulverized, it is divided into a first polyester resin group containing polyester resins that adhere to the metal particles and are extracted, and a second polyester resin group having a lower content of metal particles than the first polyester resin group.

[0100] [Appendix 10] coated metal particles comprising metal particles and polyester resin B that coats at least a portion of the metal particles; a polyester resin A present between a plurality of the coated metal particles; Composite material containing.

[0101] [Appendix 11] the content of dicyclopentenyl groups in the polyester resin B is higher than the content of dicyclopentenyl groups in the polyester resin A; 11. The composite of claim 9 or 10.

[0102] [Appendix 12] The amount of the fumaric acid component relative to the succinic acid component in the polyester resin A is greater than the amount of the fumaric acid component relative to the succinic acid component in the polyester resin B. 12. The composite material of any one of claims 9 to 11.

[0103] [Appendix 13] A rotating electric machine comprising the composite material according to any one of Supplementary Note 1 to Supplementary Note 12.

[0104] [Appendix 14] 13. A motor comprising the composite material according to any one of claims 1 to 12.

[0105] [Appendix 15] 13. A generator comprising the composite material of any one of claims 1 to 12.

[0106] [Appendix 16] A passive element comprising the composite material of any one of claims 1 to 12. [Explanation of symbols]

[0107] 1…Composite material 10...Flat magnetic metal particles 10a...Flat surface 11...metal particles 20...Polyester resin phase 21...Polyester resin A 22...Polyester resin B 30...Coated metal particles 41...First polyester resin group 42...Second polyester resin group 100…Composite material 200...Motor 210...First stator 220...First rotor 300...Transformer 400...inductor 500...Generator 510...Turbine 520...shaft 530...Second stator 540...Second rotor 550...Brush 1000...Motor system

Claims

1. A composite material comprising metal particles and a polyester resin, When the composite material is pulverized, it is divided into a first polyester resin group containing polyester resin that adheres to the metal particles and is extracted, and a second polyester resin group having a lower content of metal particles than the first polyester resin group.

2. The content of dicyclopentenyl groups in the first polyester resin group is higher than the content of dicyclopentenyl groups in the second polyester resin group. The composite material of claim 1.

3. The amount of the fumaric acid component relative to the succinic acid component in the second polyester resin group is greater than the amount of the fumaric acid component relative to the succinic acid component in the first polyester resin group. The composite material of claim 1.

4. the content of dicyclopentenyl groups in the first polyester resin group is higher than the content of dicyclopentenyl groups in the second polyester resin group, The amount of the fumaric acid component relative to the succinic acid component in the second polyester resin group is greater than the amount of the fumaric acid component relative to the succinic acid component in the first polyester resin group. The composite material of claim 1.

5. The amount of the fumaric acid component relative to the succinic acid component in the second polyester resin group is 1 to 10 times the amount of the fumaric acid component relative to the succinic acid component in the first polyester resin group. The composite material of claim 1.

6. The amount of the fumaric acid component relative to the succinic acid component in the second polyester resin group is 1 to 7 times the amount of the fumaric acid component relative to the succinic acid component in the first polyester resin group. The composite material of claim 1.

7. The metal particles contain at least one magnetic metal selected from Fe, Co, and Ni. The composite material of claim 1.

8. The metal particles are flat magnetic metal particles having a thickness of 10 nm or more and 100 μm or less, an aspect ratio of 5 or more and 10,000 or less, and a lattice distortion of 0.01% or more and 10% or less, The flat magnetic metal particles are oriented and have magnetic anisotropy in one direction within the oriented flat plane. The composite material of claim 7.

9. Coated metal particles including metal particles and a polyester resin B that coats at least a portion of the metal particles; a polyester resin A present between a plurality of the coated metal particles; A composite material comprising: When the composite material is pulverized, it is divided into a first polyester resin group containing polyester resin that adheres to the metal particles and is extracted, and a second polyester resin group having a lower content of metal particles than the first polyester resin group.

10. Coated metal particles including metal particles and a polyester resin B that coats at least a portion of the metal particles; a polyester resin A present between a plurality of the coated metal particles; A composite material comprising:

11. The content of dicyclopentenyl groups in the polyester resin B is higher than the content of dicyclopentenyl groups in the polyester resin A. The composite material of claim 10.

12. The amount of the fumaric acid component relative to the succinic acid component in the polyester resin A is greater than the amount of the fumaric acid component relative to the succinic acid component in the polyester resin B. The composite material of claim 10.

13. A rotating electric machine comprising the composite material according to any one of claims 1 to 12.

14. A motor comprising a composite material according to any one of claims 1 to 12.

15. A generator comprising a composite material according to any one of claims 1 to 12.

16. A passive component comprising a composite material according to any one of claims 1 to 12.

Citation Information

Patent Citations

  • Unidirectional transparent composite magnet and preparation method

    CN102956339A

  • Composite molded article

    JP2009202444A

  • Metal powder for soft magnetic composite material, and soft magnetic composite material

    JP2010087366A

  • Soft magnetic material, rotary electric machine, motor and electric power generator

    JP2017059816A

  • Composite magnetic particles containing metallic magnetic particles

    JP2020161753A